2014
DOI: 10.1250/ast.35.35
|View full text |Cite
|
Sign up to set email alerts
|

One-dimensional and three-dimensional propagation analyses of acoustic characteristics of Japanese and French vowel /a/ with nasal coupling

Abstract: In this paper, we describe a comparison of the acoustic characteristics of one-dimensional and three-dimensional models of vocal tracts with nasal coupling. One-dimensional acoustic propagation is computed using an electric analog model. A finite element method is used for threedimensional acoustic simulation. The comparison of these two approaches involves the vocal-tract shape of two subjects, one Japanese male and one French male pronouncing the vowel /a/ in their native language. Results show that the pole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…However, one-dimensional model of the vocal tract, i.e., an acoustic tube model, can be a simple but effective model of the vocal tract. Indeed, it is reported that the acoustic characteristics of the one-dimensional model are similar to those of a three-dimensional model at lower frequencies [7].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, one-dimensional model of the vocal tract, i.e., an acoustic tube model, can be a simple but effective model of the vocal tract. Indeed, it is reported that the acoustic characteristics of the one-dimensional model are similar to those of a three-dimensional model at lower frequencies [7].…”
Section: Introductionmentioning
confidence: 87%
“…An original vocal tract has a complicated shape [7], making it difficult to mimic its shape and behavior using a data glove. However, one-dimensional model of the vocal tract, i.e., an acoustic tube model, can be a simple but effective model of the vocal tract.…”
Section: Introductionmentioning
confidence: 99%
“…The types of models range from parametric models (e.g., Badin et al, 2005), tube or transmission-line models (e.g., Flanagan, 1972;Kelly and Lochbaum, 1962;Lim and Lee, 1993;Markel and Gray, 1976) to more elaborated wave guide and (3D)-FEM/BEM models (e.g., Matsuzaki et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For a three-dimensional (3-D) vocal-tract model based on magnetic resonance imaging (MRI) data, many extra poles in addition to formants and zeros are observed in vocal-tract transfer functions (VTTFs) [1]. Dang and Honda reported that the piriform fossa contributes strong troughs to the VTTFs, as determined from measurement experiments using an MRIbased mechanical model [2].…”
Section: Introductionmentioning
confidence: 99%
“…1. This model is constructed on the basis of vowel MRI data of the Japanese /a/ of an adult male [1]. As seen from the front view, a curved constriction indicated by an arrow is formed in the laryngeal cavity.…”
Section: Introductionmentioning
confidence: 99%